2006
DOI: 10.1002/jor.20114
|View full text |Cite
|
Sign up to set email alerts
|

Hip, knee, and ankle kinematics of high range of motion activities of daily living

Abstract: Treatment of joint disease that results in limited flexion is often rejected by patients in non-Western cultures whose activities of daily living require a higher range of motion at the hip, knee, or ankle. However, limited information is available about the joint kinematics required for high range of motion activities, such as squatting, kneeling, and sitting cross-legged, making it difficult to design prosthetic implants that will meet the needs of these populations. Therefore, the objective of this work was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
152
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(167 citation statements)
references
References 33 publications
12
152
0
Order By: Relevance
“…Although some studies have examined joint motion in kneeling activity (Mulholland and Wyss, 2001), there have been few studies which have assessed kinematics of the knee, hip, and ankle joints simultaneously, and even fewer studies looking at the kinematics of kneeling activity at these joints in the three axial planes (Hemmerich et al, 2006). To our knowledge, most studies have solely focused on kneeling activity at the knee joint (Ahlberg et al, 1988;Baltzopoulos, 1995;Hefzy et al, 1998;Nakagawa et al, 2000;Kanekasu et al, 2004;Moro-Oka et al, 2008), and the kinematics of knee having total knee arthroplasty (Coughlin et al, 2007;Hamai et al, 2008;Nakamura et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have examined joint motion in kneeling activity (Mulholland and Wyss, 2001), there have been few studies which have assessed kinematics of the knee, hip, and ankle joints simultaneously, and even fewer studies looking at the kinematics of kneeling activity at these joints in the three axial planes (Hemmerich et al, 2006). To our knowledge, most studies have solely focused on kneeling activity at the knee joint (Ahlberg et al, 1988;Baltzopoulos, 1995;Hefzy et al, 1998;Nakagawa et al, 2000;Kanekasu et al, 2004;Moro-Oka et al, 2008), and the kinematics of knee having total knee arthroplasty (Coughlin et al, 2007;Hamai et al, 2008;Nakamura et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] The provision of varus-valgus rotation at the ankle was indicated in a study of crouching in high flexion. 23 The reduced forces in our tests represent about 20% of actual forces, based on in vivo data from an instrumented TKR. 30 High flexion activities are performed less frequently than walking and with the most difficulty, but are important to many patients.…”
Section: Discussionmentioning
confidence: 95%
“…The distal tibia was hinged at the ankle joint, but the ankle was attached to the machine's frame by flexible polyurethane blocks to allow for a few degrees of varus-valgus rotations as in everyday activities. 23 The hip joint was simulated with a spherical bearing attached to a plate that was allowed to slide vertically along a smooth rail so the knee could flex to 135 8. The total vertical force at the hip was 73.4N.…”
Section: Methodsmentioning
confidence: 99%
“…Although the possible range of motion of flexion in the supine position has been stated to be 120° [14,15], there is no reported study of the hip flexion range in a sitting posture for performing functional activities. Previous kinematic studies have demonstrated that high hip flexion, i.e., 95-114°, occurs in daily activities such as sitting with legs crossed, squatting, and putting on socks, in asymptomatic subjects [16,27,28]. Thus, we selected a target bar position of 20°hip flexion from a sitting posture.…”
Section: Discussionmentioning
confidence: 99%
“…The normal angle of hip flexion is 120°in healthy people performing functional activities [14,15], and hip flexion flexibility is required to perform many daily activities, such as squatting, putting on shoes and socks, and riding a bicycle [16][17][18][19]. Since the hip joint and lumbar spine are both adjacent to the pelvis, the hip joint moves in cooperation with the lumbar spine to provide functional movement [20][21][22].…”
Section: Introductionmentioning
confidence: 99%